A new subgenus and species of Eumolpinae (Coleoptera: Chrysomelidae) from Azerbaijan, with faunistic notes on adjacent countries - Romantsov, Pavel V.; Moseyko, Alexey G. (Zootaxa, 2020)
A new monotypic subgenus, Azerberyxia new subgenus of Eryxia Baly, 1865, is described for Eryxia (Azerberyxia) serratotibialis new species, from Azerbaijan. Color photographs of the habitus and genitalia are given. New country records of Eumolpinae are provided: Macrocoma delagrangei (Pic, 1898) from Iran, Trichochrysea arnoldii (L. Medvedev, 1957) from Kazakhstan and Aphilenia interrupta Weise in Reitter, 1889 from Turkey.